Effect of Body Weight Loss on Cardiopulmonary Function Assessed by 6‐Minute Walk Test and Arterial Blood Gas Analysis in Obese Dogs. (18th December 2013) - Manens, J.; Ricci, R.; Damoiseaux, C.; Gault, S.; Contiero, B.; Diez, M.; Clercx, C.
<x xml:space="preserve">Abstract</x> Background Few studies show the detrimental effect of canine obesity on cardiopulmonary function (CPF). The 6‐Minute Walk Test (6MWT) is a noninvasive exercise test easy to perform in clinical settings. Objective The aim of this study was to investigate the effect of obesity and body weight loss (BWL) on CPF assessed by the 6MWT and arterial blood gas analysis. Animals Six experimental Beagles and 9 privately owned obese dogs were enrolled in a diet‐induced BWL program. Methods Arterial blood gas analysis and 6MWT were repeated in obese subjects (BCS 8‐9/9), in the middle of BWL (overweight, BCS 6‐7/9), and in lean dogs (BCS 5/9). Heart rate (HRp) and oxygen saturation (SpO2) were measured by pulse oximetry before the 6MWT, at midtest, and during a 5‐minute recovery period. Results Twelve dogs completed the BWL program (initial BW, 27.3 ± 2.9 kg; final BW, 20.85 ± 2.9, lsmeans ± SE, P ≤ .001). BWL caused a significant increase in 6MWT walked distance (WD; obese: 509 ± 35 m; overweight: 575 ± 36 m; lean: 589 ± 36 m; P ≤ .05). Resting arterial blood gas results were not influenced by BWL. Including all time points, obese dogs showed higher HRp and lower SpO2 compared to overweight and lean dogs. SpO2 at the end of the walk was significantly lower in obese dogs. Conclusion and Clinical Importance Obesity negatively affects 6MWT performances in dogs. The 6MWT may be used to demonstrate the efficacy of BWL to improve CPF and quality of life in obese dogs. Although BWL induced significant improvement of cardiopulmonary parameters before ideal BW, WD improved until the end of the BWL program.